2010
DOI: 10.1177/1043659610374321
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 3: Theoretical Basis for Transcultural Care

Abstract: I. INTRODUCTION A. Increasing diversity in global and local populations intensified the realization that current models of health education and health care delivery are not adequately responsive to the changing needs of populations. B. Widening health disparities across populations within countries and worldwide heightened the need for more comprehensive models and theories for care delivery that address social inequalities affecting populationbased health outcomes. C. This chapter provides a broad foundation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…A few reviews on cultural competence frameworks have been published that identify the proposed definitions and components of cultural competence (Shen 2004, Bhui et al 2007, Spitzberg & Changnon 2009, Andrews et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…A few reviews on cultural competence frameworks have been published that identify the proposed definitions and components of cultural competence (Shen 2004, Bhui et al 2007, Spitzberg & Changnon 2009, Andrews et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The students' reflections from participating in the cross-cultural training utilizing BaFa' BaFa' support the premise presented by earlier studies that gaming is effective in creating cultural awareness. Exposure to cross-cultural interactions with guided reflection can lead to awareness of cultural differences, the first steps towards awakening curiosity before competency can transpire (Andrews, et al, 2010;Graham & Richardson, 2008;Koskinen, et al, 2008). The students' reflections show that culture, imbedded in all of us, may not be an aspect of life people are conscious of even though it influences how we communicate, perceive messages and behaviors, and ultimately react Pekerti and David, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Without critical reflection, the stages of learning leading to cultural competency are not given due consideration. Leading experts in the field of cultural competence including Campinha-Bacote, Hofstede, Papdopoulos, and Leininger, have identified that cultural awareness has to be awoken before cultural knowledge, sensitivity, skill, and competence can occur (Andrews, et al, 2010;Graham & Richardson, 2008;Koskinen, Abdelhamid, & Likitalo, 2008). Awareness occurs when persons become conscious of the self in relation to others, of attitudes, beliefs, and practices: "cultural awareness is… the process of identification of culture as a phenomenon, examination of one's own biases and emotions against cultural diversity, and exploration of one's own cultural and professional background" (Koskinen, et al, 2008, p. 56).…”
Section: Cultural Issues In Healthcarementioning
confidence: 99%
“…There is a growing body of literature that seeks to provide definitional clarity; develop theoretical and conceptual frameworks; identify evidence-based and best practices; integrate cultural competence into the curricula and licensure examinations for health professions; and identify measurable outcomes that demonstrate cultural competence in health care delivery (Andrews, et al, 2010Betancourt, et al, 2003;Campinha-Bacote, 2010; National Center for Cultural Competence, 2011). The challenge to health professionals is to find credible, accurate, current, and reliable information on cultural competence, especially when seeking informa-tion that is available electronically.…”
Section: Operational Definitionsmentioning
confidence: 99%